Microchanneling on bio-inert dental ceramic using dry pulsed laser ablation and liquid supported pulsed laser ablation approach. (September 2021) - Rout, Sweta; Panigrahi, Debasish; Patel, S.K.; Dhupal, Debabrata
Highlights: An experimental inquisition of DPSS nanosecond pulsed laser microchanneling on Y-PSZ under D-PLA and LS-PLA approach. In depth study is done behind the mechanism of ablation in both the approaches. A systematic study for the effects of process parameters on channel geometrical quality is performed. A multi-objective desirability based particle swarm optimization (MOPSO) has been utilized to find out the optimal parametric conditions. The chemical and microstructural modifications around the channels are studied by SEM and EDS to compare the D-PLA and LS-PLA featured surfaces. Abstract: As the rate of heat energy transferred in yttria-partially stabilized zirconia (Y-PSZ) is very slow, it entraps the high temperature at localised region in laser microchanneling process eventually causes thermic damages which results in geometrical howlers and poor channel quality. Present work justifies, experimental inquisitions and microstructural with an aid of EDS analysis to determine the potentiality of laser ablation processes under D-PLA and LS-PLA approach. However, microchannels processed by D-PLA approach exhibit critical issues like, generation of thermal stress, frequent formation of cracks, re-deposition of eroded material and HAZ; to address these issues, a novel technique of underwater nanosecond laser micro machining was adopted. The phenomena behind the formation of channels in LS-PLA are unalike to that in D-PLA. The objective of this research is to discuss those phenomena during the study of influencing parameters over dimensional veracity of microchannels with an aid of surface integrity. In accession to that, multi-objective desirability based optimization using PSO algorithm (MOPSO) was applied to obtain the desired values of microchannel characteristics.